Thermodynamic optimization of the Dy–Nd–Fe–B system and application in the recovery and recycling of rare earth metals from NdFeB magnet. Issue 4 (27th February 2015) - Van Ende, Marie-Aline; Jung, In-Ho; Kim, Yong-Hwan; Kim, Taek-Soo
Abstract : The developed thermodynamic database for the Dy–Nd–Fe–B–Mg system enables the calculation of complex phase diagrams for the selective recovery of Nd and Dy from NdFeB magnet scrap using the liquid metal extraction process. Abstract : A critical evaluation and optimization of all reliable experimental thermodynamic properties and phase diagram data of the Dy–Nd–Fe–B system has been performed to obtain the best set of model parameters to describe the Gibbs energy of all phases in the system. Thermodynamic models with optimized model parameters can be used to predict unexplored phase diagrams and complex thermodynamic equilibria. The thermodynamic database of the Mg–Dy–Nd–Fe–B system was prepared by integrating the present model parameters to the FactSage light alloy database (FTlite) and was applied to perform comprehensive thermodynamic analyses of the selective extraction and purification process of Nd and Dy from the NdFeB permanent magnet scrap using molten Mg. Essential process parameters such as temperature, magnet to solvent ratio, vacuum pressure, heat requirement, etc . are determined in order to maximize the selective extraction of the RE metal from the magnet scrap and produce an RE alloy with low impurity content.